Pemanfaatan Vermikompos Yang Berbeda Terhadap Kelimpahan Zooplankton Pada Media Tanah Gambut - Harnita Harni; Syafriadiman '; Saberina Hasibuan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted from February to March 2017 in the Kualu Nenas village, Tambang Distric, Kampar Regency, Riau. And Analyze Identification In Water Quality Management Laboratory. The purpose of this research is to know the best abundance of zooplankton on peat soil. The method used in this research is the experimental method using complete randomized design (RAL) 1 factor with 4 treatment levels and 3 repelications. treatment used are without vermicompost (P0), vermicompost from human fecal (P1), vermicompost from cow dung (P2), vermicompost from chicken manure (P3). The results suggest that treatments is vermicompost from human fecal (P1). The results showed that got 21 zooplankton species from 4 classes that: Protozoa, Rotatoria, Crustacea, dan Insecta. classes protozoa is 1 species, than Rotatoria class 13 species, Crustacea class 5 species, and Insecta class 1 species. Zooplankton abundance best is P1 with abundance of 11439 ind/l.Keywords : vermicompost, zooplankton, peat soil